Silence please : Blockbuster in making : The art of crafting a commercial film - Nyman, Katarina (My University, 2019)
The local Finnish films have enjoyed increasing popularity in past twenty years. The Finnish film makers have gained the trust of Finnish movie audience with interesting stories the audience wants to see, and with the quality that meets the expectations of the audience. This research set out to study the product design of such an experience product as a film. The purpose of this study was to find out what is the relationship between certain product design elements of Finnish local films and the movie consumer behavior. Bridging the product design decisions of an experience product to consumer behavior increases the understanding how these decisions might affect the consumer’s interest towards the film and thus the commercial success of the film. For this purpose, the framework of signaling theory was utilized. Literary review presented all the different elements that may have an effect on the commercial success of the film. Those pre-launch elements, which are present already at the early stage of product design decision making, were selected for the empirical part of the research. To study these different film design elements in relation to consumer purchase behavior, the empirical study utilized both quantitative and qualitative research methods through method triangulation. Study utilized film statistics, exit poll studies, online panel survey and semi-structured interviews, which allowed to approach the phenomenon from different vantage points, offering a wider perspective to the consumer behavior. The empirical study revealed that the selected film elements do work as quality signals in consumer purchase process and are closely tied to the consumer’s earlier movie experiences. The quality and strength of the signal varied depending on the whole film product, its genre and how the signal fitted to the other elements around it. The study also found base for certain success signals which industry professionals use as markers to assess the commercial potential of a local film, such as the genre of the film, weather the film is based on known concept or has star actors in the lead.
Keywords: elokuva-ala, elokuvateollisuus, elämyspalvelut, elämysteollisuus, elämystuote, elämystuotemuotoilu, signaling theory